ZebraReg—a novel platform for discovering regulators of cardiac regeneration using zebrafish - Apolínová, Kateřina; Pérez, Ferran Arqué; Dyballa, Sylvia; Coppe, Benedetta; Mercader Huber, Nadia; Terriente, Javier; Di Donato, Vincenzo (Frontiers in Cell and Developmental Biology, 2024)
Cardiovascular disease is the leading cause of death worldwide with myocardial infarction being the most prevalent. Currently, no cure is available to either prevent or revert the massive death of cardiomyocytes that occurs after a myocardial infarction. Adult mammalian hearts display a limited regeneration capacity, but it is insufficient to allow complete myocardial recovery. In contrast, the injured zebrafish heart muscle regenerates efficiently through robust proliferation of pre-existing myocardial cells. Thus, zebrafish allows its exploitation for studying the genetic programs behind cardiac regeneration, which may be present, albeit dormant, in the adult human heart. To this end, we have established ZebraReg, a novel and versatile automated platform for studying heart regeneration kinetics after the specific ablation of cardiomyocytes in zebrafish larvae. In combination with automated heart imaging, the platform can be integrated with genetic or pharmacological approaches and used for medium-throughput screening of presumed modulators of heart regeneration. We demonstrate the versatility of the platform by identifying both anti-and pro-regenerative effects of genes and drugs. In conclusion, we present a tool which may be utilised to streamline the process of target validation of novel gene regulators of regeneration, and the discovery of new drug therapies to regenerate the heart after myocardial infarction.